2020
DOI: 10.1111/medu.14138
|View full text |Cite
|
Sign up to set email alerts
|

Empathy as related to gender, age, race and ethnicity, academic background and career interest: A nationwide study of osteopathic medical students in the United States

Abstract: Context:Research on associations between medical student empathy and demographics, academic background and career interest is limited, lacks representative samples and suffers from single institutional features. This study was designed to fill the gap by examining associations between empathy in patient care, and gender, age, race and ethnicity, academic background and career interest in nationwide, multi-institutional samples of medical students in the United States and to provide more definitive answers rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 35 publications
8
56
0
6
Order By: Relevance
“…Our results also concur with those of previous studies regarding the association of empathy with gender and speciality preference. The nding of higher Pre-module empathy scores for female students, although not statistically signi cant in our study, was similar to that seen in a large study based in the United States of America amongst osteopathic medicine students (38).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results also concur with those of previous studies regarding the association of empathy with gender and speciality preference. The nding of higher Pre-module empathy scores for female students, although not statistically signi cant in our study, was similar to that seen in a large study based in the United States of America amongst osteopathic medicine students (38).…”
Section: Discussionsupporting
confidence: 89%
“…Future Speciality is categorized into three broad groups: 'People-Oriented' which includes internal medicine, pediatrics, obstetrics-gynecology, family medicine, and psychiatry; 'Technology and Procedure-Oriented' which includes surgery, neurosurgery, orthopedic surgery, and public health; and 'Undecided', for students unable to identify a future speciality. This broad grouping of speciality classi cation has been used in previous empathy studies (38).…”
Section: Study De Nitionsmentioning
confidence: 99%
“…Regarding possible individual factors in uencing the development of empathy in healthcare professions, ndings from a large number of studies suggest that women are often more empathic than men, obtaining higher scores in empathy measures [15,16]. These ndings are in consonance with others performed in general population where women have shown better indicators in neurological measures related to empathy [17].…”
Section: Introductionsupporting
confidence: 69%
“…Certain genetic predisposition, evolutionary underpinnings, and interpersonal styles, but also social interactions have been described as possible explanations for such gender differences in empathic responses [18]. In medical students, personality [19], personal motivation for studying medicine [20], and career interest [15] have also been described as other in uencing factors in the development of empathy. In relation with the in uence that environment has in the development of empathy, an increasing number of studies have reported evidence supporting its in uence on empathy.…”
Section: Introductionmentioning
confidence: 99%
“…27 This scale was previously used with medical students to detect and control for the tendency to make "good impression" responses, 12,28 and in POMEE-Phase I. 13,[29][30][31]…”
Section: "Good Impression" Response Biasmentioning
confidence: 99%